AB0749 COMPARING PATIENT-PHYSICIAN DISCORDANCE IN RA AND PsA PATIENTS. (2nd June 2020) - Brites, L.; Saraiva, L.; Costa, F.; Dinis de Freitas, J.; Luis, M.; Prata, A. R.; Assunção, H.; Da Silva, J. A. P.; Rovisco, J.; Duarte, C.
Abstract : Background: Patient global Assessment (PGA) of disease activity is considered a key patient reported outcome in Rheumatoid Arthritis (RA) and Psoriatic Arthritis (PsA), both being included in combined indices of disease activity. However, patients and physicians frequently disagree in their assessment. Objectives: This study aimed at comparing the degree of this discrepancy and its determinants in RA and PsA. Methods: Cross sectional study including 100 patients with RA (ACR/EULAR 2010 criteria) and 100 patients with PsA with predominant peripheral joint involvement (CASPAR criteria), aged ≥18 years, randomly selected from the electronic registry Reuma.pt. Data were collected from the most recent rheumatology visit during the last year: sociodemographic data, disease duration (years), tender and swollen joint counts 0-28 (TJC and SJC), disease activity (DAS28 3V-PCR), erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), patient's pain assessment, PGA and physician global assessment (PhGA). The discrepancy between patients and physicians (ΔPPhGA) was defined as PGA minus PhGA, and a difference > |20mm| was taken as "discordance". Categorical variables are presented as proportions and continuous variables as mean (±SD). Patient and clinical characteristics were compared between patients with RA and PsA using t- test and χ2 test, as adequate. Variables with p<0.05 or clinically relevant were included in multivariable logistic regression analysis to identify correlates for ΔPPhGA in the whole sample. A p≤0.05 was considered statistically significant. Results: Compared to PsA, patients with RA were more often female (90% Vs 49%, p < 0.05), older (66.7 ± 10.7 Vs 58.3 ± 12.2 years, p < 0.05) and had a shorter disease duration (18.2 ± 9.8 Vs 19.9 ± 9.7 years, p = 0.202). Regarding disease activity, the RA and PsA groups were comparable: DAS28 3V-PCR (2.3 ± 0.9 Vs 2.4 ± 1.0, p = 0.34). Patients with RA had a higher mean ΔPPhGA (30.4 ± 30.6 Vs 25.4 ± 27.5, p < 0.05), and were more frequently discordant to the physician (69% Vs 51%, p < 0.05). In univariable analysis, having RA, higher patient's pain assessment and higher ESR were associated to patient-physician discordance. In multivariable analysis, only patient's pain assessment (OR 1.04 [95% CI 1.03-1.06], p = 0.00) and TJC (OR 0.82 [95% CI 0.68-0.97], p = 0.02) remained as predictors of discordance. Conclusion: Despite comparable disease activity scores in RA and PsA patients, RA patients tend to have a worst self-perception of their disease activity compared to their physician´s. Patient's pain assessment and TJC were the only predictors of patient-physician discordance, irrespective of the disease. Disclosure of Interests: Luisa Brites: None declared, LILIANA SARAIVA: None declared, Flavio Costa: None declared, João Dinis de Freitas: None declared, Mariana Luis: None declared, Ana Rita Prata: None declared, Helena Assunção: None declared, José Antonio P. da Silva Grant/research support from: Pfizer, Abbvie, Consultant of: Pfizer, AbbVie, Roche, Lilly, Novartis, João Rovisco: None declared, Catia Duarte: None declared